2012
DOI: 10.1136/bjsports-2011-090813
|View full text |Cite
|
Sign up to set email alerts
|

Influence of frequency and duration of strength training for effective management of neck and shoulder pain: a randomised controlled trial

Abstract: BackgroundSpecific strength training can reduce neck and shoulder pain in office workers, but the optimal combination of exercise frequency and duration remains unknown. This study investigates how one weekly hour of strength training for the neck and shoulder muscles is most effectively distributed.MethodsA total of 447 office workers with and without neck and/or shoulder pain were randomly allocated at the cluster-level to one of four groups; 1×60 (1WS), 3×20 (3WS) or 9×7 (9WS) min a week of supervised high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
124
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(133 citation statements)
references
References 31 publications
4
124
2
3
Order By: Relevance
“…Lowe and Dick (2015) suggested that the effect of workplace exercise is minimal and effective as tertiary prevention and therapeutic relief of neck/shoulder symptoms. Moreover, previous studies have demonstrated that specific exercise programs improves strength and resistance levels of the trunk and lumbar extensors (Andersen et al, 2012;Carvalho Mesquita, Ribeiro, & Moreira, 2012;Koumantakis, Watson, & Oldham, 2005), and these improvements appear after 6 to 8 months (Cohen, Goel, Frank, & Gibson, 1994). A 10-week yoga intervention delivered improves flexibility, state anxiety and musculoskeletal fitness in office positions workers (Cheema et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Lowe and Dick (2015) suggested that the effect of workplace exercise is minimal and effective as tertiary prevention and therapeutic relief of neck/shoulder symptoms. Moreover, previous studies have demonstrated that specific exercise programs improves strength and resistance levels of the trunk and lumbar extensors (Andersen et al, 2012;Carvalho Mesquita, Ribeiro, & Moreira, 2012;Koumantakis, Watson, & Oldham, 2005), and these improvements appear after 6 to 8 months (Cohen, Goel, Frank, & Gibson, 1994). A 10-week yoga intervention delivered improves flexibility, state anxiety and musculoskeletal fitness in office positions workers (Cheema et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…WHP programs include employee education, modified workspace designs, adjusting work habits and promoting exercise, stretches and short rest breaks. The physiologic benefits of a stretch break program include reduced intervertebral disc pressure, increased blood flow, reductions in muscle lactic acid and increased attention (Andersen et al, 2012;Balci & Aghazadeh, 2003;Cheema et al, 2013;Varatharajan et al, 2014;Zebis et al, 2011).…”
Section: Original Article (Full Paper)mentioning
confidence: 99%
“…Unfortunately, only a few studies have demonstrated that such measures had sustainable and quantifiable positive effects on symptoms and disability outcomes, although none have shown negative effects. Nonetheless, stretching exercises and resistance training programmes have emerged as highly-effective interventions to prevent office-based MSDs [23][24][25]. The general idea is that some programmes have the potential to be effective, but the scientific evidence is yet insufficient to provide the support needed in order to recommend their implementation in workplaces.…”
Section: Highlight By Alessandro Castorinamentioning
confidence: 99%
“…18 Još uvijek nije poznato koja kombinacija metoda daje najbolje rezultate, 19 a dodatni problem predstavlja pitanje njihove ekonomske isplativosti s obzirom na uloženo vrijeme. 20 Akutnu bol brže smanjuje mobilizacija kralježnice nego manipulacija tkiva ili fizioterapija.…”
Section: Sudioniciunclassified
“…20 Akutnu bol brže smanjuje mobilizacija kralježnice nego manipulacija tkiva ili fizioterapija. 21 Trening snage u trajanju od 20 tjedana, jedan sat tjedno, znatno smanjuje bol kod že-na u uredu 19 ili muškaraca u industriji. 3 Učestalo se bol u mišiću liječi vježbama snage okolnih, nebolnih mišića, a dokazano je i da jaki trening snage na bolnom miši-ću u vratu dovodi do smanjenja boli.…”
Section: Sudioniciunclassified